Good Corporate Governance dan Kinerja Keuangan Perusahaan Perbankan di Bursa Efek Indonesia - Yudhia, Putu Kevin; Widanaputra, A.A.G.P. (E-Jurnal Akuntansi; Vol 31 No 3 (2021)DO - 10.24843/EJA.2021.v31.i03.p01, 2021)
Financial performance is an achievement in a company that reflects a picture of the company's financial condition. Good Corporate Governance regulates the relationship between shareholders, directors and commissioners. The purpose of this study was to determine the effect of Good Corporate Governance on banking financial performance. This research was conducted in banking companies listed on the Indonesia Stock Exchange in the 2015-2017 period. The number of samples taken was 48 banking companies, with a purposive sampling method. The data analysis technique used is the classical assumption test and multiple linear regression test. The results of this study indicate that the board of commissioners has a negative and significant effect on financial performance. The results of this study indicate that managerial ownership has a positive and significant effect on financial performance. Keywords: Good Corporate Governance, Financial Performance, Return On Assets (ROA).